2022
DOI: 10.3389/fgene.2022.1004912
|View full text |Cite
|
Sign up to set email alerts
|

Identification of effective diagnostic biomarker and immune cell infiltration characteristics in acute liver failure by integrating bioinformatics analysis and machine-learning strategies

Abstract: Background: To determine effective biomarkers for the diagnosis of acute liver failure (ALF) and explore the characteristics of the immune cell infiltration of ALF.Methods: We analyzed the differentially expressed genes (DEGs) between ALF and control samples in GSE38941, GSE62029, GSE96851, GSE120652, and merged datasets. Co-expressed DEGs (co-DEGs) identified from the five datasets were analyzed for enrichment analysis. We further constructed a PPI network of co-DEGs using the STRING database. Then, we integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Multitranscriptome study indicated that COL4A2 is a gene specifically associated with liver fibrosis and that it positively correlates with the development of hepatic fibrosis ( 22 ). In addition, prior research has demonstrated that COL4A2 is a possible biomarker for the diagnosis of acute liver failure ( 23 ). After infection or injury, mast cells and macrophages synthesize and release the neutrophil chemokine CXCL1/CXCL2 (CXC chemokine ligand 1/2) to trigger the early stage of neutrophil recruitment in response to inflammation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multitranscriptome study indicated that COL4A2 is a gene specifically associated with liver fibrosis and that it positively correlates with the development of hepatic fibrosis ( 22 ). In addition, prior research has demonstrated that COL4A2 is a possible biomarker for the diagnosis of acute liver failure ( 23 ). After infection or injury, mast cells and macrophages synthesize and release the neutrophil chemokine CXCL1/CXCL2 (CXC chemokine ligand 1/2) to trigger the early stage of neutrophil recruitment in response to inflammation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multitranscriptome study indicated that COL4A2 is a gene specifically associated with liver fibrosis and that it positively correlates with the development of hepatic fibrosis (22). In addition, prior research has demonstrated that COL4A2 is a possible biomarker for the diagnosis of acute liver failure (23).…”
Section: Discussionmentioning
confidence: 99%